International Adaptation of a Treatment Program for Situational Couple Violence. (3rd July 2019) - Stith, Sandra M.; Spencer, Chelsea M.; Ripoll‐Núñez, Karen J.; Jaramillo‐Sierra, Ana L.; Khodadadi‐Andariyeh, Farideh; Nikparvar, Fatemeh; Oksman, Ria; Metelinen, Juha
Abstract : Intimate Partner Violence (IPV) is a serious international problem. Stith, S. M., McCollum, E. E., and Rosen, K. H. received funding from the US National Institute of Mental Health to develop and test a program for couples experiencing IPV: Domestic Violence Focused Couples Treatment (DVFCT). This article provides an overview of DVFCT, and presents three case studies illustrating how DVFCT has been adapted for use in Colombia, Iran, and Finland. This article emphasizes the need for adapting treatment models to be culturally informed, provides practice‐based evidence for DVFCT as a treatment model, and highlights the importance of careful screening and assessment when working with couples who have experienced violence, no matter the country or location where treatment is being conducted.